The Time Dividend: Top 10 Ways Artificial Intelligence is Restoring the Clock for Physicians - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The healthcare system today faces a critical challenge: physician burnout. This crisis is largely driven by the ever-increasing burden of administrative task...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care